The Impact of HIV and Malaria Coinfection: What Is Known and Suggested Venues for Further Study - Sarah Hochman; Kami Kim (Interdisciplinary Perspectives on Infectious Diseases)
HIV and malaria have similar global distributions. Annually, 500 million are infected and 1 million die because of malaria. 33 million have HIV and 2 million die from it each year. Minor effects of one infection on the disease course or outcome for the other would significantly impact public health because of the sheer number of people at risk for coinfection. While early population-based studies showed no difference in outcomes between HIV-positive and HIV-negative individuals with malaria, more recent work suggests that those with HIV have more frequent episodes of symptomatic malaria and that malaria increases HIV plasma viral load and decreases CD4+ T cells. HIV and malaria each interact with the host's immune system, resulting in a complex activation of immune cells, and subsequent dysregulated production of cytokines and antibodies. Further investigation of these interactions is needed to better define effects of coinfection.